2017
DOI: 10.1186/s13071-017-2425-9
|View full text |Cite
|
Sign up to set email alerts
|

The progression of heartworm associated respiratory disease (HARD) in SPF cats 18 months after Dirofilaria immitis infection

Abstract: BackgroundHeartworm-associated respiratory disease (HARD) in cats is induced by the arrival and death of immature adult Dirofilaria immitis in the pulmonary system and is indistinguishable from mature adult heartworm infection.MethodsA controlled, blind research study investigated the long-term (18 months post infection, PI) consequences of the inflammatory response associated with the death of immature adult heartworms in cats.Three groups of cats, 10 per group, were infected with 100 third-stage (L3) larvae … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 15 publications
0
16
0
Order By: Relevance
“…Antibody testing is the only means of identifying immature infections in cats, and cats with clinical signs are more likely to test antibody-positive than asymptomatic cats ( Lee and Atkins, 2010 ). Experimental infections have demonstrated that antibodies can persist for months after infection even if infections were abbreviated with a macrocyclic lactone 28 days after infection ( Dillon et al, 2017 ). In one study that followed a small cohort of naturally infected cats identified by positive antibody tests, cats became antibody negative up to one to three years after initial detection ( Venco et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…Antibody testing is the only means of identifying immature infections in cats, and cats with clinical signs are more likely to test antibody-positive than asymptomatic cats ( Lee and Atkins, 2010 ). Experimental infections have demonstrated that antibodies can persist for months after infection even if infections were abbreviated with a macrocyclic lactone 28 days after infection ( Dillon et al, 2017 ). In one study that followed a small cohort of naturally infected cats identified by positive antibody tests, cats became antibody negative up to one to three years after initial detection ( Venco et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…24,25,27 In experimental studies, the inflammatory response due to the death of immature adult heartworms is associated with chronic myofibrocyte proliferation, which is histologically evident in the lungs up to 18 months after infection. 28 Pulmonary arterial disease, associated with exposure to D immitis, is considered more severe in cats compared with dogs due to the increased activity of pulmonary intravascular macrophages in cats. 29,30 In one case, pathological changes in the arterial wall caused fatal dissection of the pulmonary artery ( Figures 3 and 4).…”
Section: Pathogenesis and Clinical Signsmentioning
confidence: 99%
“…Death of immature worms incites an intense inflammatory response leading to airway, interstitial and vascular changes in the pulmonary parenchyma. 5,6 Importantly, assuming no reinfection, these lesions of HARD show progressive improvement, starting 6–8 months post-infection; over time there appears to be substantial reversibility of lesions. 6 One study determined that by 18 months post-infection, there was no significant difference in the histologic grading of airways, interstitium or arteries/arterioles between cats treated with selamectin 28 days post-infection (in which ‘pre-cardiac’ third- and fourth-stage larvae were present but immature adults were killed before reaching the pulmonary arteries, thus no HARD) and cats with HARD.…”
Section: Definitions and Pathogenesismentioning
confidence: 99%
“…5,6 Importantly, assuming no reinfection, these lesions of HARD show progressive improvement, starting 6–8 months post-infection; over time there appears to be substantial reversibility of lesions. 6 One study determined that by 18 months post-infection, there was no significant difference in the histologic grading of airways, interstitium or arteries/arterioles between cats treated with selamectin 28 days post-infection (in which ‘pre-cardiac’ third- and fourth-stage larvae were present but immature adults were killed before reaching the pulmonary arteries, thus no HARD) and cats with HARD. 6 However, there was tremendous variation between cats and within lung lobes of individual cats, with some cats having lesions present, just more interspersed rather than uniform.…”
Section: Definitions and Pathogenesismentioning
confidence: 99%
See 1 more Smart Citation